Interactions of peripheral endothelin-1 and nerve growth factor as contributors to persistent cutaneous pain - Khodorova, A; Zhang, Y; Nicol, G; Strichartz, G (Physiological research, 2018)
Endothelin-1 (ET-1) and Nerve Growth Factor (NGF) are proteins, released from cancer-ridden tissues, which cause spontaneous pain and hypersensitivity to noxious stimuli. Here we examined the electrophysiological and behavioral effects of these two agents for evidence of their interactions. Individual small-medium cultured DRG sensory neurons responded to both ET-1 (50 nM, n=6) and NGF (100 ng/ml, n=4), with increased numbers of action potentials and decreased slow K(+) currents; pre-exposure to ET-1 potentiated NGF´s actions, but not vice versa. Behaviorally, single intraplantar (i.pl.) injection of low doses of ET-1 (20 pmol) or NGF (100 ng), did not increase hindpaw tactile or thermal sensitivity, but their simultaneous injections sensitized the paw to both modalities. Daily i.pl. injections of low ET-1 doses in male rats caused tactile sensitization after 21 days, and enabled further tactile and thermal sensitization from low dose NGF, in ipsilateral and contralateral hindpaws. Single injections of 100 ng NGF, without changing the paw's tactile sensitivity by itself, acutely sensitized the ipsilateral paw to subsequent injections of low ET-1. The sensitization from repeated low ET-1 dosing and the cross-sensitization between NGF and ET-1 were both significantly greater in female than in male rats. These findings reveal a synergistic interaction between cutaneously administered low doses of NGF and ET-1, which could contribute to cancer-related pain.
Keywords: Endothelin-1; bolest; Pain; Pain Measurement; Touch; Physical Stimulation; Protein Binding; nervový růstový faktor; Female; hmat; Nerve Growth Factor; injekce subkutánní; endotelin-1; krysa rodu Rattus; zvířata; Injections, Subcutaneous; potkani Sprague-Dawley; ženské pohlaví; fyzikální stimulace; Male; vazba proteinů; Rats; Rats, Sprague-Dawley; Animals; mužské pohlaví; měření bolesti